Aplikasi Rekomendasi Tempat Makan Menggunakan Algoritma Slope One pada Platform Android - Dharma Pratama; Seng Hansun (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
Food is one of the basic needs for human being. The needs of food will always increase unanimous with the number of people, so that many restaurants appear. Because of there are so many restaurants, it can arise a confusion when we want to choose a restaurant to eat. Therefore, an application which can give a restaurant recommendation will be built in this research. The recommendation given by the system is calculated using Slope One algorithm and the restaurants database is gathered from Google Places API. Slope One algorithm make the recommendation by summing the rating of a restaurants with the difference average to other restaurants. The application also had been tested to the user by using J.R.Lewis questionnaire with questions categories of application usefulness, information quality, and user interface quality. The results from the testing are user find the application useful to give the proper restaurant recommendation, the information quality is good, and the user interface quality is also good.